Nontraumatic Clostridium septicum Myonecrosis in Adults: Case Report and a 15-Year Systematic Literature Review. Issue 6 (November 2016) - Forrester, Joseph D.; Shkolyar, Eugene; Gregg, David; Spain, David A.; Weiser, Thomas G.
Abstract : Abstract: Clostridium septicum is a spore-forming anaerobic gram-positive rod capable of causing rapidly progressive nontraumatic myonecrosis. A case of nontraumatic C. septicum myonecrosis (ntCSM) is described. A systematic review of all published cases of ntCSM from 2000–2015 was performed. Twenty-three cases of ntCSM were identified. The median age was 67 years (range, 26–84 years) and 15 (68%) were men. Only 5 (21%) patients had multifocal disease. Diabetes mellitus was the most common preexisting medical condition present in 9 (39%) patients. Occult colon cancer was frequently associated with ntCSM and most commonly right-sided colon cancer (69%). Only 10 (42%) patients survived. Clostridium septicum myonecrosis is a surgical emergency associated with morbidity and mortality. Rapid and aggressive debridement remains the cornerstone of care, although mortality has changed little in the last 30 years, suggesting an opportunity for improving diagnosis, treatment, or both.